Abchazja Fazila Iskandera — muzułmańska tradycja i kultura, sowieckie czasy - Kończar, Izabela (Przegląd Rusycystyczny, 2006)
АБХАЗИЯ ФАЗИЛЯ ИСКАНДЕРА — МУСУЛЬМАНСКАЯ ТРАДИЦИЯ И КУЛЬТУРА, СОВЕТСКИЕ ВРЕМЕНА Резюме Данная статья посвящена вопросу содействования элементов мусульманских и советских затронутых в романе Фазиля Искандера Сандро из Чегема. Анализу подвергаются следующие общественные явления: кровная месть, религиозные запреты есть свинину и пить алкоголь, многоженство. Описываются отношения абхазцев и советских властей ко всем этим обычаям. Много места посвящено также ритуалам, связанным со смертью и похоронами (таким как, напр., оплакивание, забота о умерших). Кроме того статья указывает на исторические события и лица, использованные Искандером в романе (Дикая дивизия, имам Чечни и Дагестана — Шамиль, И. В. Сталин, Н. А. Лакоба). FAZIL ISKANDER’S ABKHAZIA — MUSLIM TRADITION AND CULTURE, SOVIET TIMES Summary The publication provides an analysis of selected cultural phenomena characteristic for the Muslim world that are described in Fazil Iskander’s novel Sandro from Tchegem. The following customs are analysed: polygamy, ban on eating pork and drinking alcohol, the rule of clan vengeance. The author devotes much space to elaborate on rich sepulchral rites and its realisation on the Abkhazian ground. The aim of the article is to show the attitude of both the Abkhazians and Soviet authorities to the above mentioned rituals and customs as well as to indicate changes that highlanders’ ceremonial underwent under the Soviet infl uence. Moreover, the article contains descriptions of historical events and individuals that had a substantial impact on the course of history in Abkhazia (Wild division, the imam of Chechnya and Dagestan — Shamil, N. A. Łakoba, J.W. Stalin, W. I. Lenin).